Review of the management of Acute Alcohol Withdrawal - Butterworth, Katrina (Journal of General Practice and Emergency Medicine of Nepal, 2010)
NICE is a British organization, the National Institute for Health and Clinical Excellence, which reviews the evidence for the diagnosis and management of many different clinical conditions. The guidelines produced are based on the evidence found in the international literature and are used in the UK as a baseline for excellent clinical practice.In this journal we will give summaries of topics covered by NICE, together with some tips on how you may need to adjust them based on the local realities in Nepal. You can access the full guidelines yourself by going to: www.nice. org.uk